Fluent solution of an air flow through rectangular curved channel duct [electronic resource] - Muhammad Hadi Ibrahim, 1987- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia , 2010